Intraoperative Vancomycin Powder Reduces Staphylococcus aureus Surgical Site Infections and Biofilm Formation on Fixation Implants in a Rabbit Model. Issue 5 (May 2018) - Hovis, James Paul; Montalvo, Ryan; Marinos, Dimitrius; Joshi, Manjari; Shirtliff, Mark E.; O'Toole, Robert V.; Manson, Theodore T.
Abstract : Objectives: To evaluate the effectiveness of intraoperative vancomycin powder in prevention of surgical site infection and biofilm formation on implants in a contaminated animal fixation model. Methods: We created a rabbit surgical model including fixation implants at a tibial surgical site seeded with methicillin-resistant Staphylococcus aureus . Our study cohort included 18 rabbits. Nine received vancomycin powder at the surgical site, and the other 9 did not. Serum vancomycin levels were measured at scheduled time points over 24 hours. Bone infection and implant biofilm formation were determined based on the number of colony-forming units present 2 weeks after surgery. Radiography, histology, and electron microscopy aided in evaluation. Results: No bone infection or implant colonization occurred in the vancomycin powder group. Six bone infections and 6 implant biofilm formations (67%; 95% confidence interval, 45%–88%) occurred in the group that did not receive vancomycin powder ( P = 0.009). Serum vancomycin levels were detectable at minimal levels at 1 and 6 hours only. Pathological changes occurred in the specimens that were positive for infection. Conclusions: Intraoperative vancomycin powder application at the time of fixation decreases risk for bone infection and biofilm formation on implants in a rabbit model, with minimal increase in serum vancomycin levels. The results are encouraging and support the rationale for a clinical trial investigating the use of local vancomycin powder to reduce the rate of surgical site infections. Clinical Relevance: Infection is a common complication of surgery, especially with implants. Simple methods to prevent or decrease the occurrence of infection would benefit the patient and the health care system. Abstract : Supplemental Digital Content is Available in the Text.